2021
DOI: 10.18502/espoch.v1i2.9513
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Dosages of Biofertilizers Composed of Mycorrhizae and Diazotrophs on the Corn Productivity

Abstract: Corn (Zea mays L.) is a crop of world importance, however, one of the problems present during its development is the lack of nutrients or the presence of these in a form not available to the plant. Because of this, the objective of this review article is to gather information on the influence of different dosages of mycorrhiza and diazotroph biofertilizers on the corn crop. A meticulous bibliographic research was carried out, detailing the methods used by various authors; Among the most repetitive and signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…The presence of saprotrophic microorganisms can significantly affect AMF activity [19] and vice versa [20]. However, it has also been reported that the mixture of AMF with other microorganisms (bacteria or fungi) favors the absorption of nutrients by plants [21,22], and the control of phytopathogenic fungi [23,24]. AMF has been studied under different scenarios, for example, under controlled conditions [25,26], in greenhouses [27], in experimental fields [4,28,29], regions [12,16] and even on a global scale [30].…”
Section: Introductionmentioning
confidence: 99%
“…The presence of saprotrophic microorganisms can significantly affect AMF activity [19] and vice versa [20]. However, it has also been reported that the mixture of AMF with other microorganisms (bacteria or fungi) favors the absorption of nutrients by plants [21,22], and the control of phytopathogenic fungi [23,24]. AMF has been studied under different scenarios, for example, under controlled conditions [25,26], in greenhouses [27], in experimental fields [4,28,29], regions [12,16] and even on a global scale [30].…”
Section: Introductionmentioning
confidence: 99%